Education Services for Special Intelligent and Talent Children in Elementary School - Liza Murniviyanti; Asep Supena (AL-ISHLAH: Jurnal Pendidikan, 2021)
Special intelligent children and special talents require special treatment and handling in the world of education. This study aims to describe the educational services for special intelligent children and special talents at Baptist Elementary School Palembang. This study used a qualitative method with a field research approach. Data collection techniques were observation, interviews, recording and documentation. The data source used the primary data source because the researchers took the data directly in the field, namely Elementary School Baptist Palembang. Respondents in this study were 8 people that were 1 person as the head of Palembang Baptist Elementary School, 2 accompanying teachers for special intelligent and special talent children and 5 students who are categorized as special intelligent children and special talents. The findings obtained are 1) the process of educational services for special intelligent children and special talents at Baptist Elementary School Palembang. 2) Factors inhibiting and supporting the learning process of special intelligent children and special talents at Baptist Elementary School Palembang. 3) The teacher's strategy in dealing with special intelligent children and special talents at Palembang Baptist Elementary School